Understanding the healthfulness of outlets providing lunch and dinner meals: a census of a rural food retail environment in Victoria, Australia. (21st December 2020) - Alston, Laura; Versace, Vincent; Brown, Emily; Nichols, Melanie; Whelan, Jill; Bolton, Kristy A.; Sacks, Gary; Needham, Cindy; Orellana, Liliana; Allender, Steven
Abstract: Objective : To undertake a census of the healthfulness of food venues providing lunch or dinner meals in a rural Australian setting and compare healthfulness by remoteness, using two measurement tools. Methods : A census of the rural local government area food venues was undertaken using two validated tools: the Healthfulness Rating Classification System (HRCS) and the Nutrition Environment Measures Survey (NEMS‐R). Data were collected covering an area of 3, 438 square kilometres in Victoria, Australia, with a population of >21, 000. Healthfulness by remoteness was described and variability between tools was explored. Results : Data were collected from all 95 eligible food venues. Both tools classified the food venues as relatively unhealthy. The mean HRCS score was ‐2.9 (unhealthy) and the mean NEMS‐R score was 10.8 (SD 7.0; possible range ‐27 to 64). There were no significant differences in healthiness of venues by remoteness (as measured by the Modified Monash Model), although the outer‐rural region had lower scores. Conclusions : This census of a rural food retail environment showed low access to healthy menu options along with minimal provision of nutrition information and promotion of healthy food in food venues. This environment has the potential to affect the dietary intake of more than 21, 000 rural‐dwelling Australians and action to improve rural food environments is desperately needed. Implications for public health : If unhealthful rural food environments are not addressed, inequalities in the diet‐related disease burden for rural Australians will continue to persist. This study shows that interventions are needed for independent venues that could be targeted by researchers, local health promotion officers, community nutritionists or community education programs.